Rosmarinus officinalis essential oil triggers depression followed by CNS excitability in Wistar rats - Bastos de Araújo, Daniella; Raiol de Almeida, Ysis Nayhara; Otake Hamoy, Maria Klara; Vasconcelos de Souza, Luana; Pacheco Hartcopff, Priscille Fidelis; Gonçalves dos Santos, Rodrigo; Santos da Silva, Lívia Letícia; Lima da Rocha, Lucas; Farias dos Santos, Murilo; da Silva Deiga, Yris; da Cunha Ferreira, Rayllan; Vieira de Souza, Raíssa; et al. (Frontiers in Natural Products, 2024)
The essential oil of rosemary (Rosmarinus officinalis) (EORO) is widely used in folk medicine and has proven therapeutic effects. Our research evaluated high doses of rosemary essential oil in 54 Wistar rats between 180 and 200 g. The study consisted of three experiments: 1) behavioral monitoring of the animals after administration of 500 mg/kg i.p.; 2) electrocorticographic records after drug administration; 3) anticonvulsant drug reaction, where phenytoin, phenobarbital, and diazepam 10 mg/kg i.p were applied. The results showed that the application of EORO presented two phases. Phase 1 was characterized by the appearance of myorelaxation and a reduction in the power of the electrocorticogram in low-frequency cerebral oscillations. Phase 2 was characterized by increased excitability, with the appearance of convulsions and the increased power of electrocorticographic recordings in cerebral oscillations up to 40 Hz. In this phase, three tracing patterns were observed. Beta oscillations were the most prevalent and were better controlled by diazepam, which demonstrates that the excitatory activity of EORO is related to the reduction of GABAergic activity.